2013
DOI: 10.3109/07357907.2013.845671
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LDOC1 Expression by Promoter Methylation in Cervical Cancer Cells

Abstract: Cervical cancer lacks reliable prognostic factors for both progression and chemotherapeutic responsiveness. The expression of the LDOC1 tumor suppressor candidate was therefore investigated. In four of six cervical cancer cell lines tested, expression of LDOC1 was silenced. Downregulation of LDOC1 could also be shown in biopsies of cervical cancer specimens. PCR-based promoter methylation analysis revealed a significant association between promoter methylation and the loss of LDOC1 expression, which could be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…4 These data suggest the possibility that the increased expression of GNL3L, particularly in gastric cancer, may be due to the absence of inhibitory activity of LDOC1 owing to promoter hyper-methylation. 22,30 Furthermore, analysis of in vivo expression pattern of GNL3L and LDOC1 in various primary cancers from BioXpress database indicates an inverse correlation (Fig. 11), supporting the notion that the interplay between GNL3L and LDOC1 may be critical for cell growth control.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…4 These data suggest the possibility that the increased expression of GNL3L, particularly in gastric cancer, may be due to the absence of inhibitory activity of LDOC1 owing to promoter hyper-methylation. 22,30 Furthermore, analysis of in vivo expression pattern of GNL3L and LDOC1 in various primary cancers from BioXpress database indicates an inverse correlation (Fig. 11), supporting the notion that the interplay between GNL3L and LDOC1 may be critical for cell growth control.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, we have characterized Leucine Zipper Downregulated in Cancer-1 (LDOC1) as a novel interacting partner of GNL3L that can modulate the stimulatory effect exerted on NF-kB by GNL3L. LDOC1 is a 17-kDa protein that is down-regulated in most pancreatic, gastric and cervical cancer cell lines 21,22 and is a negative regulator of NFkB. 23 The present investigation provides evidence that LDOC1-mediated GNL3L destabilization leads to decreased total cellular p65 pool, which in-turn results in reduced cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA-seq analysis revealed that SB induced the expression of several tumor suppressor genes were repressed due to hypermethylation or Loss of Heterozygosity (LOH) as indicated in Table 3. The X-chromosome methylation pattern also has been affected as indicated by the increased LDOC1 expression, a gene whose promoter known to be hypermethylated in cancer [54]. However, a detailed methylation-specific sequencing and analysis needs to be carried out to further gain a deeper insight onto differential methylation effects of SB.…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, LDOC1 is a potential biomarker and putative therapeutic target for osteosarcoma. Consistent with its role as a tumor suppressor gene, decreased expression of LDOC1 has been shown in several other types of cancers, including prostate cancer, 16 cervical cancer, 17 ovarian cancer, 18 oral squamous cell carcinoma, 19 and thyroid cancer. 13 LDOC1 has been reported to be involved in regulation of proliferation and apoptosisin cancer.…”
Section: Introductionmentioning
confidence: 78%